Assessing the therapeutic potential of astaxanthin in experimental proliferative vitreoretinopathy models - Savas, Hakan Veli; Yildirim, Hakan; Ilhan, Nevin; Eroksuz, Yesari; Erdag, Murat; Canleblebici, Mehmet; Balbaba, Mehmet (Sage Publications Ltd, 2025)
Purpose: This study evaluates the effectiveness of astaxanthin in treating experimental proliferative vitreoretinopathy (PVR) in rats. Methods: Fifty-six Sprague Dawley rats were divided into 4 groups. PVR was induced using dispase and astaxanthin was administered intravitreally at concentrations of 10 ng/mu L and 100 ng/mu L. The effects on TGF-ss, VEGF, PDGF, FGF2 and IL-1 ss were measured by ELISA and retinal changes were analysed histopathologically and immunohistochemically. Results: Astaxanthin at 10 ng/mu L and 100 ng/mu L administered to the treatment groups significantly decreased TGF-beta, VEGF, FGF2, IL-1, and PDGF levels compared to the sham group (p < 0.05). At the 100 ng/mu L dose, more significant decreases were observed, especially in PDGF and IL-1 levels (p < 0.01). Histopathologic scoring revealed that the treated groups had significantly lower PVR scores than the Sham group, with the highest dose showing the greatest improvement (p < 0.01). Furthermore, treated groups exhibited improved retinal architecture and reduced fibrotic tissue formation. Immunohistochemical staining for VEGF was positive in all groups except Control, with no significant differences in VEGF expression intensity between groups. Conclusion: Astaxanthin effectively reduces both biochemical and histopathological markers of PVR, highlighting its potential as a novel therapeutic agent for managing this challenging condition in clinical practice.
Keywords: Astaxanthin; proliferative vitreoretinopathy; experimental model; growth factors